Mitosis Methods & Protocols - CarloAlberto Redi (European Journal of Histochemistry, 2010)
<!--StartFragment--> Mitosis Methods & Protocols Andrew D. McAinsh (Edt) Humana press, Totowa, New Jersey (USA) Series: Springer Protocols Methods in Molecular Biology, Volume 545, 2009 ISBN: 978-1-60327-992-5   It is quite clear from the contents of this book that the remarkably fascinating phenomenon of mitosis (that captured, and still is capturing, the attention of entire generations of scientists) is still open to research. This is mainly due to our lack of knowledge of so many multifaced events of this extraordinarly complex process. The reader giving a glace through the Contents and Contributors sections is speechless: All of the first-class models (i.e., budding yeast, Caenorabditis, Drosophila, Xenopus and Human) are presented..... <!--EndFragment-->